Education return and financing: Donated affluence as consequence of tuition free study programs in Germany - Hans-Georg Petersen; Markus Kirchner (Universität Potsdam, Lehrstuhl Finanzwissenschaft, 2008)
The paper sheds some light on the education returns in Germany in the post war period. After describing higher education in Germany the current stand of higher education financing within the single states is presented. In six states tuition fees will be introduced in 2007/08 and discussions are going on in even some more. In the second part of the paper an empirical analysis is done using longitudinal data from the German social pension system. The analysis over the whole lifecycle renders results which proof that the higher education advantages are quite remarkable and might be a justification for more intensified financing by tuition fees. But all this has to be embedded into an encompassing strategy of tax and social policy, especially to prevent a strengthened process of social selection, which would be counterproductive for an increased and highly qualified human capital in Germany.
urn:nbn:de:kobv:517-opus-26969
Keywords: D1; D14; H81; I21; I22; I28; J13; J24; J26; 370; Education return; tuition fees; tertiary education; vocational education; human capital; lifetime income; income contingent loans; Bildungsertrag; Erwerbsverlauf; Studienfinanzierung; Bildungsinvestition; Bildungschancen; Deutschland